Uji Efektivitas Bakteri Asam Laktat yang diisolasi dari Cairan Fermentasi Biji Kopi Robusta (Coffea Canephora) Sebagai Kandidat Probiotik - Yanti, Devi Novi; Syam, Husain; Sukainah, Andi (Jurnal Pendidikan Teknologi Pertanian, 2024)
This research is an experimental study that aims to determine the lactic acid bacteria (LAB) isolated from the fermented liquid of robusta coffee beans as probiotic candidates. Parameters observed in the probiotic potency test of LAB isolates were antimicrobial activity, tolerance to pH conditions of gastric, intestinal and bile salts as well as autoaggregation and coaggregation. The results showed that from 10 isolates of lactic acid bacteria, 3 isolates were obtained, namely BT0I5, BT3I7 and BT48I1 which have the potential to be probiotic candidates because they meet the criteria as probiotics, namely having antimicrobial activity against pathogenic bacteria (Bacillus cereus and Salmonella), able to survive in gastric acid pH conditions, intestinal pH and bile salts and has positive autoaggregation ability against Lactobacillus casei and Lactobacillus plantarum and positive coaggregation against test bacteria, namely Bacillus cereus and Salmonella by forming a precipitate at the bottom of the tube and the supernatant looks clear